Biological Activities and Flavonoid Content of Different Parts of Phaleria Macrocarpa (Scheff.) Boerl Fruit Extracts - Hendra, Rudi (2011)
Phaleria macrocarpa (Scheff.) Boerl (Family Thymelaceae) posses several bioactivities and is used as traditional medicine in Indonesia. Investigation on antioxidant, anti-inflammatory and antimicrobial activities are still lacking. The aims of this study were therefore to determine those biological activities of methanolic, ethyl acetate, hexane and hot water extract from pericarp, mesocarp, and seed of P. macrocarpa fruit and quantitative analysis of total phenolics and flavonoids present in the various bioactive extracts. The methanolic, ethyl acetate and hexane extracts of pericarp showed free radical scavenging activity (71.9±1.9, 88.1 ± 2.5 and 78.2± 1.7%) at concentration of 300 μg/ml and these results were lower as compared to butylated hydroxytoluene (BHT), ascorbic acid and α-tocopherol (antioxidant standards). The methanolic, ethyl acetate and hot water extracts of pericarp showed high reducing power with values 92.5±0.1, 84.7±0.3 and 91.9±0.1%, respectively at 300 μg/ml. All parts of P. macrocarpa fruit showed low to moderate level of nitric oxide inhibitory activity in IFN-γ/LPS activated RAW 264.7 cell line with values of 15.6±1.0% to 75.0±0.7% at concentration of 200 μg/ml without cytotoxic to the cells. In addition, methanol and ethyl acetate extract of P. macrocarpa fruits at 1.5 and 3 mg/disc showed variable inhibitory activity against both Gram-positive and Gram-negative bacteria with inhibition zone diameters ranging from 0.32-2.33 cm exclusive of paper disc (0.6 cm). While, ethyl acetate extract of P. macrocarpa fruits at 3 mg/well showed variable inhibitory activity against all fungi tested with inhibition zone diameters ranging from 0.4-2.13 cm exclusive of well diameter (0.6 cm). The total phenolic contents analysis showed that ethyl acetate extract of seed contained the highest amount of total phenolic at 60.94±0.81 mg GAE/g DW while the lowest amount was observed in hexane extract of pericarp at 32.97±0.69 mg GAE/g DW. Furthermore, methanolic extract of pericarp contained the highest amount of total flavonoids with a value of 161.35±1.59 mg rutin equivalent/g DW and the lowest was observed in hexane extract of seed with a value of 9.66±0.07 mg rutin equivalent/g DW. Quantitative analysis of flavonoid compounds from P. macrocarpa fruit (pericarp, mesocarp and seed) were performed by using reversed-phase high performance liquid chromatography (RP-HPLC) technique. The results showed that kaempferol, myricetin, naringin, quercetin and rutin were present in all different part of P. macrocarpa fruit. Thus, the present results showed that P. macrocarpa fruit (pericarp, mesocarp and seed) poses antioxidant, anti-inflammatory and antimicrobial activities might be due to the present of flavonoid and phenolic compounds.